Pseudocapacitance multiporous vanadyl phosphate/graphene thin film electrode for high performance electrochemical capacitors - Hu, Bingbing; Xu, Chuanlan; Yu, Danmei; Chen, Changguo (Journal of colloid and interface science, 2021)
[Display omitted] •MP-VOPO4@rGO binder-free thin film electrode is first successfully synthesized.•The MP-VOPO4@rGO has more active sites and low internal resistance.•The dual strategy design enable accelerate ion diffusion and electron transfer.•The surface pseudocapacitive process is predominant in the total capacitance. Supercapacitors are being considered as promising electricity storage devices with green sustainable energy conversion. To efficiently develop and optimize pseudocapacitive material of vanadyl phosphate, herein, multiporous vanadyl phosphate/graphene (denoted as MP-VOPO4@rGO) is fabricated for the first time with phytic acid as a phosphorus source by extremely simple sol-gel and drop coating methods, and used as the free binder thin film electrode of supercapacitors. The smart combination of honeycomb-like architecture and graphene incorporation results in more active sites and low internal resistance, significantly improving energy storage performance. The effect of introducting polystyrene (denoted as PS) template and rGO on the performance of the nanocomposite is systematically analyzed by comparing the performance of the corresponding thin film electrodes. The MP-VOPO4@rGO thin film electrode delivers superior pseudocapacitive performance of 672 F g−1 at 1 A g−1 as well as a remarkable rate capability of 552 F g−1 at 5 A g−1, and it presents a remarkable longterm cycling stability, with a capacitance retention of 83.5% after 5000 cycles. Very interestingly, the results of surface capacitance contribution dominance clearly demonstrates its rapid capacitive response. In addition, based on MP-VOPO4@rGO thin film as positive and negative electrodes, the corresponding assembled symmetric supercapacitors exihibits outstanding energy density of 26.3 Wh kg−1 at power density of 249.9 W kg−1. This investigation can not only provide a versatile strategy to design other thin film electrode materials but also open up a new insight into the development of polyanion phosphate composites for next-generation high performance energy storage systems.